The economic benefits of surgical site infection prevention in adults: a systematic review. Issue 1 (September 2020) - McFarland, A.; Reilly, J.; Manoukian, S.; Mason, H.
Summary: Background: Surgical site infections (SSIs) present a significant burden to healthcare and patients in terms of excess length of stay, distress, disability and death. SSI risk and the associated economic burden may be reduced through adherence to prevention guidelines although the irreducible minimum is unclear. Aim: To evaluate the methods used to estimate the cost-effectiveness of prevention strategies for all SSIs. Methods: PubMed, Medline, CINAHL, and UK National Health Service Economic Evaluation Database were searched from inception to January 2020 to identify English language economic evaluation studies, embedded economic evaluations, and studies with some analysis in relation to cost and benefit in adult patients receiving surgical care in any setting. Risk of bias was assessed using two published checklists. Findings: Thirty-two studies involving 24, 043 participants were included. Most studies evaluated SSI prevention in orthopaedic surgeries. Antibiotic prophylaxis, screening, treating, or decolonization of meticillin-resistant Staphylococcus aureus and surgical wound closure were the main methods evaluated. Methods ranged from cost-analyses to cost-effectiveness and cost-utility analyses. Synthesis of results was not possible due to heterogeneity. All studies reported some economic benefit associated with preventing SSI; however, measures of benefit were not reported consistently and the quality of studies was low to moderate. Limited evidence in relation to SSI impact on quality of life was identified. Conclusion: Current evidence in relation to the economic benefits of SSI prevention is limited. Further robust studies that utilize sound economic and epidemiological methods are required to inform future investment decisions in SSI prevention.